2021
DOI: 10.18196/jai.v22i2.10775
|View full text |Cite
|
Sign up to set email alerts
|

Income Diversification and Financial Performance: The Mediating Effect of Banks’ Size, Ownership Structure and the Financial Crisis in Vietnam

Abstract: Research aims: This study focuses on the correlation between income diversification and financial performance, taking into account banks’ size and type of ownership as well as financial crisis.Design/Methodology/Approach: This study uses financial data of 29 commercial banks in Vietnam during the period from 2005 to 2018. This research employs an Generalized Method of Moments (GMM) regression.Research findings: The results do not find a statistical evidence of a direct effect of banks’ income diversification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Third, the capital buffer ratio (CBR) indicates changes in banks' capitalization levels due to capital regulations (Illueca et al, 2022;Jiang et al, 2020;Jiang & Yuan, 2022;Quyen et al, 2021). By influencing borrowers, we anticipate that a more excellent BCB ratio will decrease bank risk-taking and boost financial stability.…”
Section: Capitalizationmentioning
confidence: 99%
“…Third, the capital buffer ratio (CBR) indicates changes in banks' capitalization levels due to capital regulations (Illueca et al, 2022;Jiang et al, 2020;Jiang & Yuan, 2022;Quyen et al, 2021). By influencing borrowers, we anticipate that a more excellent BCB ratio will decrease bank risk-taking and boost financial stability.…”
Section: Capitalizationmentioning
confidence: 99%
“…Therefore, hypothesis 3 is put forward. Hypothesis 3: there is a positive correlation between equity checks and balances and financing efficiency, that is, Z index is negatively correlated with financing efficiency [15].…”
Section: Hypothesis Of Equity Balance and Financing Efficiencymentioning
confidence: 99%
“…For example, several studies have indicated that CSR disclosure levels remain very low (Vu and Pratoomsuwan, 2019;Thuy, 2019;Huong et al, 2019). Hang et al (2020) and Quyen et al (2021) also uncovered that firm size, age, and type of auditing firm positively affected the level of CSR disclosure. However, few studies focus on the influence of CSRD on FP.…”
Section: Affiliationmentioning
confidence: 99%